Aqueous film-forming foam extinguishing agent based on short fluorocarbon chain
By synergistically designing modified short-chain fluorocarbon surfactants with nano-silica, and combining them with modified guar gum and chitosan, the problems of environmental friendliness, stability, and limited functionality of traditional aqueous film-forming foam fire extinguishing agents have been solved, achieving multifunctional and environmentally friendly fire extinguishing effects and industrial production capabilities.
Patent Information
- Application Number
- CN202511435331.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2025-12-05
AI Technical Summary
Traditional aqueous film-forming foam fire extinguishing agents suffer from poor biodegradability, easy stratification and sedimentation, limited functionality, difficulty in balancing foam stability and film-forming efficiency, agglomeration of nano-silica, and uneven dispersion of flame retardants. These issues make it difficult to meet the environmental protection, comprehensive performance, and process stability requirements of modern fire prevention and control.
The design employs a synergistic approach of modified short-chain fluorocarbon surfactants and nano-silica, with pretreatment using silane coupling agents to enhance dispersibility, combined with modified guar gum and chitosan to strengthen foam stability, and the addition of corrosion inhibitors and antifreeze agents. The optimized preparation process ensures component uniformity and fire extinguishing effectiveness.
It achieves improvements in environmental friendliness, balances foam stability and film-forming properties, and enhances multifunctionality. It is suitable for various flammable liquid fires and does not freeze in low-temperature environments, making it suitable for large-scale industrial production.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fire extinguishing agents, in particular to a water film forming foam fire extinguishing agent based on short fluorocarbon chains. BACKGROUND
[0002] In the field of fire extinguishing agents, water film forming foam fire extinguishing agents have become the core product for preventing and controlling oil fires and flammable liquid fires because they have the dual effects of foam covering and water film insulation. Traditional water film forming foam fire extinguishing agents rely on long fluorocarbon chain surfactants to build a film system, which can form a stable water film, but there are two key defects: first, long fluorocarbon chain substances have poor biodegradability and are easy to accumulate in the environment, which does not meet the current environmental regulations for fire extinguishing agents "low environmental risk"; second, the compatibility of long fluorocarbon chain surfactants with water and co-surfactants is limited, and layering and precipitation easily occur during preparation, resulting in poor batch stability of the product.
[0003] At the same time, existing products generally have the problem of difficulty in balancing foam stability and film forming efficiency: in order to improve the foam holding time, the amount of high molecular weight foam stabilizer is often increased, but excessive foam stabilizer will increase the viscosity of the system, hindering the rapid spreading of the water film on the oil surface; if the amount of foam stabilizer is reduced, the foam is easily broken by high temperature of the flame and cannot continuously cover the fire point. In addition, traditional fire extinguishing agents have a single function, although they can achieve fire extinguishing, they lack long-term protection for metal parts of the fire extinguishing system, and are prone to freezing in low temperature environments, limiting their application in cold regions.
[0004] On the other hand, the existing preparation process lacks control over the dispersibility of raw materials: functional fillers such as nano-silicon dioxide are prone to agglomeration due to high surface energy and cannot be uniformly dispersed in the system, resulting in a decrease in the density of the water film; solid powders such as flame retardants are difficult to dissolve and disperse in high viscosity systems, and are prone to form local concentration unevenness, affecting the stability of the flame retardant effect. These problems together make it difficult for traditional water film forming foam fire extinguishing agents to meet the modern demand for "high efficiency, environmental protection, and multi-functionality" in fire prevention and control in terms of environmental protection, comprehensive performance, and process stability, and new formulations and processes need to be developed to break through these problems. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application provides a water film forming foam fire extinguishing agent based on short fluorocarbon chains, which solves the problems of poor film forming property, unstable foam, and single performance of traditional foam fire extinguishing agents.
[0006] To achieve the above purpose, the present application is realized by the following technical scheme:
[0007] A kind of water film-forming foam extinguishing agent based on short fluorocarbon chain, comprising the following raw materials by weight: 8-12 parts of modified short fluorocarbon chain surfactant, 5-8 parts of dodecyl dimethyl betaine, 50-60 parts of deionized water, 2-4 parts of modified guar gum, 4-6 parts of ethylene glycol, 1-2 parts of benzotriazole, 0.5-1 part of sodium bicarbonate, 0.3-0.5 part of dimethicone, 3-5 parts of decabromodiphenyl ethane, 1-2 parts of sodium carboxymethyl cellulose, 0.5-1 part of disodium ethylenediaminetetraacetate, 0.2-0.4 part of isothiazolinone, 0.5-1 part of nano silicon dioxide.
[0008] Further, the nano silicon dioxide is hydrophobic nano silicon dioxide pretreated by silane coupling agent KH-550, with a BET specific surface area of 150-200 m² / g and a purity of ≥99.8%, and the pretreatment process is as follows: the nano silicon dioxide is added to a 6% silane coupling agent KH-550 ethanol solution, with a solid-liquid mass ratio of 1:8, stirred at 250 r / min for 30 min, then dried in a 85℃ vacuum drying oven for 3 h, and cooled for standby. The pretreatment of silane coupling agent KH-550 reduces its surface energy, avoids agglomeration and enhances hydrophobicity, so that it is uniformly dispersed in the system, cooperates with the modified short fluorocarbon chain surfactant to improve the water film density, and at the same time improves the compatibility with organic components, ensures uniform and stable film formation, and prolongs the effective action time of the water film.
[0009] Further, the modified short fluorocarbon chain surfactant has the following specific preparation steps:
[0010] A1, perfluorohexyl ethyl acrylate copolymer is added to a three-necked flask containing ethanol, stirred at 200-250 r / min and heated to 60-70℃ to completely dissolve it, hydroxyethyl methacrylate and ammonium persulfate are added, stirred uniformly, then heated to 80-85℃ and reacted for 4-5 h, cooled to room temperature after reaction, the product is precipitated with deionized water, filtered, and the precipitate is dried in a 60-70℃ vacuum drying oven for 8-10 h to obtain the first modified short fluorocarbon chain surfactant; hydroxyethyl methacrylate introduces hydroxyethyl ester groups, improves the compatibility of the surfactant with water and other components, solves the problem of easy layering of traditional long fluorocarbon chain surfactants, and lays a foundation for subsequent modification.
[0011] A2, the first modified short carbon fluoride chain surfactant is added into a three-necked flask containing acetone, stirred at 200-250 r / min until completely dissolved and the temperature is controlled at 40-50℃, toluene diisocyanate is slowly added dropwise, the dropwise adding time is 1-1.5 h, and the stirring speed is 150-200 r / min during the dropwise adding process, toluene diisocyanate has high reactivity, and low-speed stirring avoids local rapid crosslinking to form a gel; after the dropwise adding is completed, the stirring is continued for 2-3 h, then triethanolamine is added, the temperature is increased to 60-65℃, the stirring is continued at 200-250 r / min for 3-4 h, after the reaction is completed, the acetone is removed by distillation under reduced pressure, and the second modified short carbon fluoride chain surfactant is obtained; toluene diisocyanate and triethanolamine cooperatively construct a three-dimensional crosslinking network, the structural stability of the surfactant is enhanced, the surfactant is not easy to decompose under high-temperature flame, the effective period of fire extinguishing is prolonged, and the surface activity is further optimized.
[0012] A3, the nano-titanium dioxide is added into a mixed solvent of ethanol and water in a volume ratio of 1:1, ultrasonic dispersion is performed for 30-40 min to form a uniform dispersion liquid, the silane coupling agent KH-550 is added, the stirring is uniformly performed at 250-300 r / min, and then heating is performed to 70-80℃ for 2-3 h, so that the nano-titanium dioxide dispersion liquid modified by the silane coupling agent is obtained; the second modified short carbon fluoride chain surfactant is added into the dispersion liquid, the stirring is continued for 4-5 h, so that the two are tightly combined through physical adsorption and chemical bonding, after the reaction is completed, the centrifugal separation is performed to collect the precipitate, the precipitate is washed with ethanol for 3-4 times, and drying is performed in a vacuum drying box at 80-90℃ for 10-12 h, so that the modified short carbon fluoride chain surfactant is obtained. The nano-titanium dioxide is compounded with the surfactant, the film forming compactness and uniformity are strengthened, the water film effect of air isolation is improved, the biodegradability is enhanced, and the environmental residue is reduced.
[0013] Further, the amount ratio of the perfluorohexyl ethyl acrylate copolymer, ethanol, hydroxyethyl methacrylate and ammonium persulfate in A1 is 10-15 g: 100-150 mL: 30-40 g: 2-3 g.
[0014] Further, the amount ratio of the acetone, toluene diisocyanate and triethanolamine in A2 is 80-100 mL: 6-12 g: 5-8 g.
[0015] Further, the amount ratio of the nano-titanium dioxide, the mixed solvent of ethanol and water and the silane coupling agent KH-550 in A3 is 5-8 g: 100-120 mL: 3-5 g.
[0016] Further, the toluene diisocyanate used in the A2 is a mixture of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, the mass ratio of which is 3:1, and when the toluene diisocyanate is added dropwise, the dropwise addition speed is controlled to be 0.5 mL / min through a constant pressure dropping funnel, and the temperature fluctuation of the reaction system is ensured to be not more than ±2℃. The 3:1 ratio of the toluene diisocyanate mixture optimizes the reaction activity and cross-linking effect; the dropwise addition speed of 0.5 mL / min and the temperature fluctuation control avoid the uneven structure of the product caused by local violent reaction, ensure the formation of a stable three-dimensional cross-linked network, and improve the batch consistency and performance stability of the surfactant.
[0017] Further, the modified guar gum has the following specific preparation steps:
[0018] B1, the guar gum is added to a three-necked flask containing isopropyl alcohol and stirred uniformly at 200-250 r / min, and gentle stirring is used to promote swelling and avoid high-speed stirring to cause molecular chain rupture; sodium hydroxide is added, the temperature is raised to 50-60℃, and stirring is performed at 150-200 r / min for 1-1.5 h, so that the alkali solution uniformly infiltrates the guar gum and activates the hydroxyl group fully; then propylene oxide is slowly added dropwise, the dropwise addition time is 1-2 h and the temperature is kept at 60-70℃, after the dropwise addition is completed, the reaction is continued at 70-75℃ for 3-4 h, the pH is adjusted to neutral with hydrochloric acid after the reaction is completed, the filter cake is washed with isopropyl alcohol for 2-3 times after filtration, and drying is performed in a vacuum drying oven at 60-70℃ for 6-8 h to obtain the first modified guar gum; the etherification modification of propylene oxide is gradually performed at 60-70℃, the water solubility of the guar gum is adjusted, and the problem of insufficient foam stability caused by excessive water solubility is solved, which lays a foundation for subsequent modification.
[0019] B2, the first modified guar gum is added to a three-necked flask containing deionized water, stirred at 250-300 r / min, and heated to 70-80℃ to completely dissolve and form a uniform solution, acrylamide, potassium persulfate and N,N'-methylene bisacrylamide are added, and after uniform stirring, nitrogen is introduced to remove air, and the reaction is performed at 80-85℃ for 4-5 h under nitrogen protection to promote the graft copolymerization of acrylamide; after the reaction is completed, the temperature is cooled to room temperature, the product is precipitated with ethanol, and after filtration, the precipitate is dried in a vacuum drying oven at 70-80℃ for 8-10 h to obtain the second modified guar gum; N,N'-methylene bisacrylamide constructs a lightly cross-linked network to form a foam skeleton with elasticity and toughness, which greatly improves the high-temperature impact resistance of the foam and prevents the foam from being broken under the flame.
[0020] B3, the chitosan is added into the acetic acid solution with a mass fraction of 1%, stirred at 200-250 r / min until completely dissolved to form a chitosan acetic acid solution, the second modified guar gum is added into the solution and stirred uniformly, heated to 50-60℃, and the glutaraldehyde is slowly added dropwise at a stirring speed of 150-200 r / min; the glutaraldehyde has high crosslinking activity, and low-speed stirring can avoid the formation of hard agglomerates in local areas and ensure the uniformity of the composite system; after the dropwise addition is completed, the stirring is continued for 2-3 h, the reaction is ended, the pH is adjusted to neutral by using a sodium hydroxide solution, the precipitate is collected by centrifugal separation, washed with deionized water for 3-4 times, and dried in a vacuum drying box at 60-70℃ for 8-10 h to obtain the modified guar gum; the hydrogen bonding of the chitosan cooperates with the guar gum, further enhances the foam stability and conformability, improves the environmental protection, makes the foam more conformable to the fire point interface, and strengthens the cooling and insulation effects.
[0021] Further, the amount ratio of the guar gum, isopropyl alcohol, sodium hydroxide and propylene oxide in B1 is 20-25 g: 90-110 mL: 2-3 g: 25-35 g.
[0022] Further, the amount ratio of the deionized water, acrylamide, potassium persulfate and N,N'-methylene bisacrylamide in B2 is 80-100 mL: 15-25 g: 1-2 g: 0.5-1 g.
[0023] Further, the amount ratio of the chitosan, acetic acid solution and glutaraldehyde in B3 is 5-8 g: 60-80 mL: 0.6-1 mL.
[0024] A preparation method of a water film forming foam extinguishing agent based on a short fluorocarbon chain, specifically comprising the following steps:
[0025] S1, the deionized water is purified by ion exchange resin for standby use; the nanometer silicon dioxide is dried in a vacuum drying box at 100-110℃ for 2-3 h for standby use, the drying activates the surface of the nanometer silicon dioxide and reduces weak agglomeration, facilitating subsequent dispersion;
[0026] S2, the purified deionized water is added into a reaction kettle, stirred at 200-300 r / min, and then the dodecyl dimethyl betaine, ethylene glycol, benzotriazole, sodium bicarbonate, ethylenediaminetetraacetic acid disodium salt and isothiazolinone are sequentially added, heated to 40-50℃ and stirred for 30-40 min until uniform; the stirring speed is kept, and the decabromodiphenyl ethane powder is slowly added and stirred until uniformly dispersed; the stirring speed is kept, and the sodium carboxymethyl cellulose is slowly added and stirred until the system forms a uniform fluid and the viscosity at 40-50℃ reaches 100-300 mPa·s, without visible particles or stratification;
[0027] S3, adding modified short fluorocarbon chain surfactant and modified guar gum to the above system, increasing the stirring speed to 400-500 r / min, and increasing the temperature to 60-70 DEG C and stirring for 2-3 h until uniform; adding the pretreated nano-silicon dioxide, keeping the stirring speed and temperature and continuing to stir for 1-1.5 h until uniformly dispersed;
[0028] S4, adding polydimethylsiloxane to the system and stirring until uniform; then transferring the material to a high-pressure homogenizer, under the conditions of a pressure of 20-30 MPa and a temperature of 50-60 DEG C, homogenizing for 5-10 min each time, and homogenizing for 2-3 times to form a uniform and stable emulsion;
[0029] S5, transferring the homogenized emulsion to a maturation tank, and standing at room temperature for maturation for 12-24 h; after maturation, degassing the emulsion at 40-50 DEG C under vacuum for 1-1.5 h, the vacuum degree is -0.08 to -0.09 MPa, to remove residual trace bubbles in the system; then filtering with a 0.45 mu m filter membrane to remove impurities and particles that are not uniformly dispersed, and filling into a sealed container to obtain the short fluorocarbon chain-based water film-forming foam extinguishing agent.
[0030] Further, the maturation process in S5 needs to be protected by nitrogen, the nitrogen flow is 0.5 L / min, and the pressure in the maturation tank is maintained at 0.1 MPa.
[0031] The application provides a short fluorocarbon chain-based water film-forming foam extinguishing agent, which has the following beneficial effects:
[0032] 1. The modified short fluorocarbon chain surfactant is used to replace the traditional long fluorocarbon chain surfactant, which solves the environmental residue problem of the traditional extinguishing agent from the root. The short fluorocarbon chain structure has strong surface activity and good biodegradability, and can be gradually decomposed into harmless substances through microbial action in the natural environment, the biodegradation rate is improved, and the short fluorocarbon chain structure will not accumulate in the soil and water, which fully meets the requirements of the European Union and domestic environmental protection standards for "low environmental risk extinguishing agent". At the same time, the modified short fluorocarbon chain surfactant, the hydroxyethyl ester group, the three-dimensional cross-linked network and the nano-titanium dioxide composite layer introduced in the molecular structure greatly improve the compatibility of the short fluorocarbon chain surfactant with water, dodecyl dimethyl betaine and other components, effectively avoiding the problem of stratification and precipitation of the traditional long fluorocarbon chain surfactant due to strong hydrophobicity, and improving the reliability in fire fighting application.
[0033] 2、The product breaks through the technical contradiction of traditional fire extinguishing agent that film forming is fast but foam is easy to break, and film forming is slow but foam is stable, through the synergistic effect of modified short fluorocarbon chain surfactant, nano silicon dioxide and modified guar gum. On the one hand, the modified short fluorocarbon chain surfactant can quickly reduce the surface tension of water, and the nano silicon dioxide pretreated by silane coupling agent KH-550 can quickly spread on the oil surface to form a uniform and dense water film, which can quickly isolate the contact between flame and air and inhibit the reignition of oil fire. On the other hand, the guar gum modified by etherification, graft copolymerization and composite chitosan three times, through the synergistic effect of the lightly crosslinked polyacrylamide network and the hydrogen bond of chitosan, a foam skeleton with elasticity and toughness is constructed, which prolongs the half-life of the foam, and even under the high temperature impact of the flame, the foam can still maintain the complete structure, continuously cover the fire point and play the cooling role.
[0034] 3、The present application realizes the multifunctional integration of "fire extinguishing-equipment protection-environment adaptation" through scientific raw material ratio and modification design, and breaks through the limitation of single function of traditional fire extinguishing agent. In addition to the core function of fire extinguishing, the corrosion inhibitor benzotriazole and the chelating agent disodium ethylenediaminetetraacetate in the product form a synergistic corrosion inhibition system. At the same time, the antifreeze agent ethylene glycol added in the formula will not freeze and stratify even in the storage of northern cold regions, solving the problem of poor low temperature applicability of traditional fire extinguishing agent. In addition, the complex effect of flame retardant decabromodiphenyl ethane and nano silicon dioxide makes the foam not only isolated by water film, but also inhibited by the synergistic effect of gas phase flame retardant of flame retardant and solid phase flame retardant of nano particles, further inhibiting the spread of flame, which is suitable for various flammable liquid fires such as gasoline, diesel and ethanol, and the scene adaptability is far beyond that of single function fire extinguishing agent.
[0035] 4、The preparation process of the present application is optimized through multiple links, which not only guarantees the stability of product quality, but also has the potential for large-scale industrial production. In the raw material pretreatment stage, deionized water is purified by ion exchange resin and nano silicon dioxide is vacuum dried and activated, which effectively avoids the interference of impurity ions and nano particle agglomeration on the system; when the basic components are mixed, the components are uniformly distributed and the system viscosity is stably controlled at 100-300 mPa•s; after the core components are mixed, the modified short fluorocarbon chain surfactant, modified guar gum and nano silicon dioxide form a uniform colloidal dispersion system through high pressure homogenization treatment. In addition, the nitrogen protection and vacuum degassing process in the curing stage effectively removes the residual microbubbles in the system, avoiding the problem of discontinuous water film caused by bubble rupture during fire extinguishing. The whole process parameters are clear and controllable, and each link can be accurately controlled by automatic equipment, which can meet the batch supply demand of large-scale fire fighting enterprises. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0037] Embodiment 1, preparation of water film forming foam extinguishing agent based on short fluorocarbon chain, the specific preparation steps are as follows:
[0038] S1, deionized water is purified by ion exchange resin for standby; nanometer silicon dioxide is dried in a vacuum drying oven at 100℃ for 2h for standby;
[0039] S2, 50 parts of purified deionized water is added into a reaction kettle, stirred at 200r / min, 5 parts of dodecyl dimethyl betaine, 4 parts of ethylene glycol, 1 part of benzotriazole, 0.5 parts of sodium bicarbonate, 0.5 parts of ethylenediaminetetraacetic acid disodium, 0.2 parts of isothiazolinone are added in turn, heated to 40℃ and stirred for 30min to be uniform; keep the speed, slowly add 3 parts of decabromodiphenyl ethane powder, stir until dispersed uniformly; continue to keep the speed, slowly add 1 part of sodium carboxymethyl cellulose, stir until the system forms a uniform fluid and the viscosity at 40℃ reaches 100mPa•s, no visible particles or stratification;
[0040] S3, 8 parts of short fluorocarbon chain surfactant and 2 parts of guar gum are added to the above system, the stirring speed is increased to 400r / min, and the temperature is increased to 60℃ and stirred for 2h to be uniform; 0.5 parts of pretreated nanometer silicon dioxide is added, the speed and temperature are kept and continue to stir for 1h to be dispersed uniformly;
[0041] S4, 0.3 parts of polydimethylsiloxane is added to the system and stirred uniformly; then the material is transferred to a high pressure homogenizer, under the conditions of pressure 20MPa and temperature 50℃, homogenized for 5min each time, homogenized for 2 times, to form a uniform and stable emulsion;
[0042] S5, the homogenized emulsion is transferred to a maturation tank, and is left to mature at room temperature for 12h, nitrogen protection is required during the process, the nitrogen flow is 0.5L / min, and the pressure in the maturation tank is maintained at 0.1MPa; after maturation, the emulsion is vacuum degassed at 40℃ for 1h, the vacuum degree of degassing is-0.08MPa, to remove the residual trace bubbles in the system; then filtered with a 0.45μm filter membrane to remove impurities and particles not dispersed uniformly, and then filled into a sealed container, to obtain the water film forming foam extinguishing agent based on short fluorocarbon chain.
[0043] Embodiment 2, preparation of water film forming foam extinguishing agent based on short fluorocarbon chain, the specific preparation steps are as follows:
[0044] S1, the deionized water is purified by ion exchange resin for standby; nanometer silicon dioxide is dried in a vacuum drying box at 110°C for 3h for standby;
[0045] S2, 60 parts of purified deionized water is added in a reaction kettle, stirring at 300r / min, 8 parts of dodecyl dimethyl betaine, 6 parts of ethylene glycol, 2 parts of benzotriazole, 1 part of sodium bicarbonate, 1 part of ethylenediaminetetraacetic acid disodium, 0.4 parts of isothiazolinone are added in turn, and the temperature is raised to 50°C and stirred for 40min to be uniform; keep the speed, slowly add 5 parts of decabromodiphenyl ethane powder, stir until dispersed uniformly; continue to keep the speed, slowly add 2 parts of sodium carboxymethyl cellulose, stir until the system forms a uniform fluid and the viscosity at 50°C reaches 300mPa•s, no visible particles or stratification;
[0046] S3, 12 parts of short fluorocarbon chain surfactant and 4 parts of guar gum are added to the above system, the stirring speed is increased to 500r / min, the temperature is raised to 70°C, and stirring is carried out for 3h to be uniform; 1 part of pretreated nanometer silicon dioxide is added, and stirring is continued at the same speed and temperature for 1.5h to be dispersed uniformly;
[0047] S4, 0.5 parts of polydimethylsiloxane is added to the system and stirred uniformly; then the material is transferred to a high-pressure homogenizer, and homogenized under the conditions of pressure 30MPa and temperature 60°C, each time for 10min, and homogenized for 3 times to form a uniform and stable emulsion;
[0048] S5, the homogenized emulsion is transferred to a maturation tank, and is left to mature at room temperature for 24h, during which nitrogen protection is required, the nitrogen flow is 0.5L / min, and the pressure in the maturation tank is maintained at 0.1MPa; after maturation, the emulsion is vacuum degassed at 50°C for 1.5h, the vacuum degree of degassing is-0.09MPa, to remove the residual trace bubbles in the system; then filtered with a 0.45μm filter membrane to remove impurities and particles not dispersed uniformly, and then filled into a sealed container, to obtain a short fluorocarbon chain based water film forming foam extinguishing agent.
[0049] Example 3, preparation of short fluorocarbon chain based water film forming foam extinguishing agent, the specific preparation steps are as follows:
[0050] S1, the deionized water is purified by ion exchange resin for standby; nanometer silicon dioxide is dried in a vacuum drying box at 105°C for 2.5h for standby;
[0051] S2, 55 parts of purified deionized water was added into the reaction kettle, stirring at 250 r / min, 6 parts of dodecyl dimethyl betaine, 5 parts of ethylene glycol, 1 part of benzotriazole, 0.7 parts of sodium bicarbonate, 0.7 parts of ethylenediaminetetraacetic acid disodium, 0.3 parts of isothiazolinone were added in turn, and the temperature was raised to 45℃ and stirred for 35 min until uniform; keep the speed, slowly add 4 parts of decabromodiphenyl ethane powder, stir until dispersed uniformly; continue to keep the speed, slowly add 1 part of sodium carboxymethyl cellulose, stir until the system forms a uniform fluid and the viscosity at 45℃ reaches 200 mPa·s, no visible particles or stratification;
[0052] S3, 10 parts of short fluorocarbon chain surfactant and 3 parts of guar gum were added to the above system, the stirring speed was increased to 450 r / min, the temperature was raised to 65℃ and stirred for 2.5 h until uniform; 0.7 parts of pretreated nano silicon dioxide was added, and the stirring was continued at the same speed and temperature for 1.2 h until dispersed uniformly;
[0053] S4, 0.4 parts of polydimethylsiloxane was added to the system and stirred uniformly; then the material was transferred to a high-pressure homogenizer, and homogenized under the conditions of pressure 25 MPa and temperature 55℃ for 7 min each time, and homogenized for 3 times to form a uniform and stable emulsion;
[0054] S5, the homogenized emulsion was transferred to a maturation tank, and was left to stand at room temperature for maturation for 18 h, nitrogen was introduced into the process, the nitrogen flow was 0.5 L / min, and the pressure in the maturation tank was maintained at 0.1 MPa; after maturation, the emulsion was vacuum degassed at 45℃ for 1.2 h, the vacuum degree of degassing was-0.09 MPa, to remove the residual trace bubbles in the system; then filtered with a 0.45 μm filter membrane to remove impurities and particles not dispersed uniformly, and then filled into a sealed container, to obtain a short fluorocarbon chain based water film forming foam extinguishing agent.
[0055] Example 4, preparation of modified short fluorocarbon chain surfactant, the specific preparation steps are as follows:
[0056] A1, 10 g of perfluorohexyl ethyl acrylate copolymer was added to a three-necked flask containing 100 mL of ethanol, stirred at 200 r / min and heated to 60℃ to completely dissolve it, 30 g of hydroxyethyl methacrylate and 2 g of ammonium persulfate were added, stirred uniformly, then the temperature was raised to 80℃ and reacted for 4 h, after the reaction was completed, the temperature was cooled to room temperature, the product was precipitated with deionized water, filtered, and the precipitate was dried in a vacuum drying oven at 60℃ for 8 h to obtain the first modified short fluorocarbon chain surfactant;
[0057] A2, the first modified short carbon fluoride chain surfactant is added into a three-necked flask containing 80 mL of acetone, stirred at 200 r / min until completely dissolved and the temperature is controlled at 40°C, 6 g of toluene diisocyanate is slowly added dropwise, the dropping time is 1 h, and the stirring speed is 150 r / min during the dropping, after the dropping is completed, the stirring is continued for 2 h, then 5 g of triethanolamine is added, the temperature is increased to 60°C, and the stirring is continued at 200 r / min for 3 h, after the reaction is completed, the acetone is removed by distillation under reduced pressure, and the second modified short carbon fluoride chain surfactant is obtained;
[0058] A3, 5 g of nano-titanium dioxide is added into 100 mL of ethanol-water mixed solvent with a volume ratio of 1:1, ultrasonic dispersion is performed for 30 min to form a uniform dispersion liquid, then 3 g of silane coupling agent KH-550 is added, the stirring is uniformly performed at 250 r / min, and then the temperature is increased to 70°C for reaction for 2 h, the nano-titanium dioxide dispersion liquid modified by the silane coupling agent is obtained, the second modified short carbon fluoride chain surfactant is added into the dispersion liquid, and the stirring is continued for 4 h, after the reaction is completed, the precipitation is collected by centrifugal separation, the precipitation is washed with ethanol for 3 times, and the precipitation is dried in a vacuum drying box at 80°C for 10 h, and the modified short carbon fluoride chain surfactant is obtained.
[0059] Example 5, the modified short carbon fluoride chain surfactant is prepared, and the specific preparation steps are as follows:
[0060] A1, 15 g of perfluorohexyl ethyl acrylate copolymer is added into a three-necked flask containing 150 mL of ethanol, the stirring is performed at 250 r / min and the temperature is increased to 70°C until the perfluorohexyl ethyl acrylate copolymer is completely dissolved, 40 g of hydroxyethyl methacrylate and 3 g of ammonium persulfate are added, the stirring is uniformly performed, the temperature is increased to 85°C, and the reaction is performed for 5 h, after the reaction is completed, the temperature is cooled to room temperature, the product is precipitated by deionized water, the precipitation is filtered, and the precipitation is dried in a vacuum drying box at 70°C for 10 h, and the first modified short carbon fluoride chain surfactant is obtained;
[0061] A2, the first modified short carbon fluoride chain surfactant is added into a three-necked flask containing 100 mL of acetone, stirred at 250 r / min until completely dissolved and the temperature is controlled at 50°C, 12 g of toluene diisocyanate is slowly added dropwise, the dropping time is 1.5 h, and the stirring speed is 200 r / min during the dropping, after the dropping is completed, the stirring is continued for 3 h, then 8 g of triethanolamine is added, the temperature is increased to 65°C, and the stirring is continued at 250 r / min for 4 h, after the reaction is completed, the acetone is removed by distillation under reduced pressure, and the second modified short carbon fluoride chain surfactant is obtained;
[0062] A3, 8 g of nano-titanium dioxide was added into 120 mL of ethanol-water mixed solvent with a volume ratio of 1:1, ultrasonic dispersion was performed for 40 min to form a uniform dispersion liquid, 5 g of silane coupling agent KH-550 was added, and after uniform stirring at 300 r / min, heating was performed to 80℃ for 3 h to obtain a nano-titanium dioxide dispersion liquid modified by the silane coupling agent, the second modified short fluorocarbon chain surfactant was added into the dispersion liquid, and stirring reaction was continuously performed for 5 h, after the reaction was completed, centrifugal separation was performed to collect the precipitate, washing was performed with ethanol for 4 times, and drying was performed in a vacuum drying box at 90℃ for 12 h to obtain the modified short fluorocarbon chain surfactant.
[0063] Example 6, preparation of modified guar gum, the specific preparation steps are as follows:
[0064] B1, 20 g of guar gum was added into a three-necked flask containing 90 mL of isopropyl alcohol, and stirring was performed at 200 r / min until uniform, 2 g of sodium hydroxide was added, and heating was performed to 50℃, and stirring was performed at 150 r / min for 1 h, then 25 g of propylene oxide was slowly added dropwise, the dropwise adding time was 1 h, and the temperature was kept at 60℃, after the dropwise adding was completed, 70℃ was kept for 3 h, after the reaction was completed, the pH was adjusted to neutral with hydrochloric acid, and after filtration, the filter cake was washed with isopropyl alcohol for 2 times, and drying was performed in a vacuum drying box at 60℃ for 6 h to obtain the first modified guar gum;
[0065] B2, the first modified guar gum was added into a three-necked flask containing 80 mL of deionized water, stirring was performed at 250 r / min, and heating was performed to 70℃ until it was completely dissolved to form a uniform solution, 15 g of acrylamide, 1 g of potassium persulfate and 0.5 g of N,N'-methylene bisacrylamide were added, after uniform stirring, nitrogen was introduced to remove air, and reaction was performed at 80℃ for 4 h under the protection of nitrogen, after the reaction was completed, cooling was performed to room temperature, the product was precipitated with ethanol, after filtration, the precipitate was dried in a vacuum drying box at 70℃ for 8 h to obtain the second modified guar gum;
[0066] B3, 5 g of chitosan was added into 60 mL of 1% acetic acid solution, and stirring was performed at 200 r / min until it was completely dissolved to form a chitosan acetic acid solution, the second modified guar gum was added into the solution and stirred uniformly, heating was performed to 50℃, and 0.6 mL of glutaraldehyde was slowly added dropwise at a stirring speed of 150 r / min, after the dropwise adding was completed, stirring reaction was continuously performed for 2 h, after the reaction was completed, the pH was adjusted to neutral with sodium hydroxide solution, centrifugal separation was performed to collect the precipitate, washing was performed with deionized water for 3 times, and drying was performed in a vacuum drying box at 60℃ for 8 h to obtain the modified guar gum.
[0067] Example 7, preparation of modified guar gum, the specific preparation steps are as follows:
[0068] B1, 25 g guar gum was added to a three-necked flask containing 110 mL of isopropyl alcohol and stirred at 250 r / min until uniform, 3 g of sodium hydroxide was added, the temperature was raised to 60°C, and stirred at 200 r / min for 1.5 h, then 35 g of propylene oxide was slowly added dropwise, the dropwise addition time was 2 h and the temperature was maintained at 70°C, after the dropwise addition was completed, the reaction was continued at 75°C for 4 h, after the reaction was completed, the pH was adjusted to neutral with hydrochloric acid, the filter cake was washed with isopropyl alcohol for 3 times, and dried in a vacuum drying oven at 70°C for 8 h to obtain the first modified guar gum;
[0069] B2, the first modified guar gum was added to a three-necked flask containing 100 mL of deionized water, stirred at 300 r / min and heated to 80°C to completely dissolve to form a uniform solution, 25 g of acrylamide, 2 g of potassium persulfate and 1 g of N,N'-methylene bisacrylamide were added, stirred uniformly, then nitrogen was introduced to remove air, and reacted at 85°C for 5 h under nitrogen protection, after the reaction was completed, the product was precipitated with ethanol, the precipitate was filtered and dried in a vacuum drying oven at 80°C for 10 h to obtain the second modified guar gum;
[0070] B3, 8 g of chitosan was added to 80 mL of 1% acetic acid solution, stirred at 250 r / min until completely dissolved to form a chitosan acetic acid solution, the second modified guar gum was added to the solution and stirred uniformly, heated to 60°C, and 1 mL of glutaraldehyde was slowly added dropwise at a stirring speed of 200 r / min, after the dropwise addition was completed, the reaction was continued for 3 h, after the reaction was completed, the pH was adjusted to neutral with sodium hydroxide solution, the precipitate was collected by centrifugal separation, washed with deionized water for 4 times, and dried in a vacuum drying oven at 70°C for 10 h to obtain the modified guar gum.
[0071] Comparative Example 1, a short fluorocarbon chain based water film forming foam extinguishing agent was prepared, the specific preparation steps were as follows:
[0072] The remaining steps were unchanged, only the short fluorocarbon chain surfactant of Example 3 was replaced with the modified short fluorocarbon chain surfactant prepared in Example 4, and a short fluorocarbon chain based water film forming foam extinguishing agent was prepared.
[0073] Comparative Example 2, a short fluorocarbon chain based water film forming foam extinguishing agent was prepared, the specific preparation steps were as follows:
[0074] The remaining steps were unchanged, only the guar gum of Example 3 was replaced with the modified guar gum prepared in Example 7, and a short fluorocarbon chain based water film forming foam extinguishing agent was prepared.
[0075] Comparative Example 3, a short fluorocarbon chain based water film forming foam extinguishing agent was prepared, the specific preparation steps were as follows:
[0076] The remaining steps are unchanged, only the short fluorocarbon chain surfactant of Example 3 is replaced by the modified short fluorocarbon chain surfactant prepared in Example 4, and the guar gum is replaced by the modified guar gum prepared in Example 7, to prepare a short fluorocarbon chain based water film forming foam extinguishing agent.
[0077] Performance test
[0078] Test item Test standard Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Film forming time (s) GB 15308-2006 45 38 32 22 25 15 Foam half-life (min) GB 15308-2006 5.2 6.8 8.5 12.3 14.8 18.6 Fire extinguishing time (s) GB 15308-2006 128 105 82 65 58 42 Anti-freezing property (-25℃, 48h) GB 15308-2006 Slight freezing, no delamination after thawing No freezing, no delamination No freezing, no delamination No freezing, no delamination No freezing, no delamination No freezing, no delamination Metal corrosion rate (mm / a) (Q235 steel sheet, 50℃ immersion for 30d) GB 15308-2006 0.085 0.076 0.069 0.063 0.058 0.052 Biodegradation rate (28d, %) (CO2 production method) GB / T 21856-2008 32.6 41.8 47.2 68.7 72.1 85.4
[0079] According to the performance test results, in the short fluorocarbon chain based water film forming foam extinguishing agent related tests, the film forming time of the extinguishing agent of Examples 1-3 without using modified raw materials is 32-45s, the foam half-life is 5.2-8.5min, the extinguishing time is 82-128s, the metal corrosion rate is 0.069-0.085mm / a, the biodegradation rate is 32.6%-47.2%, and only Example 1 is slightly frozen at-25℃ for 48h in terms of frost resistance; while the modified short fluorocarbon chain surfactant and the modified guar gum are used respectively or simultaneously in Comparative Examples 1-3, the performance is significantly better, the film forming time is shortened to 15-25s, the foam half-life is extended to 12.3-18.6min, the extinguishing time is reduced to 42-65s, the metal corrosion rate is reduced to 0.052-0.063mm / a, the biodegradation rate is increased to 68.7%-85.4%, and the frost resistance is all no freezing and no delamination, indicating that the application of the modified short fluorocarbon chain surfactant and the modified guar gum can greatly optimize the film forming, foam stability, extinguishing efficiency, corrosion resistance, environmental protection and frost resistance of the extinguishing agent.
[0080] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways to replace, as long as they do not deviate from the invention or exceed the scope defined by the present claims, which shall belong to the protection scope of the present application.
Claims
1. A water-based film-forming foam extinguishing agent based on short fluorocarbon chains, characterized in that: The composition comprises the following raw materials by weight: 8-12 parts of modified short fluorocarbon chain surfactant, 5-8 parts of dodecyl dimethyl betaine, 50-60 parts of deionized water, 2-4 parts of modified guar gum, 4-6 parts of ethylene glycol, 1-2 parts of benzotriazole, 0.5-1 part of sodium bicarbonate, 0.3-0.5 part of dimethicone, 3-5 parts of decabromodiphenyl ethane, 1-2 parts of sodium carboxymethyl cellulose, 0.5-1 part of disodium ethylenediaminetetraacetate, 0.2-0.4 part of isothiazolinone, and 0.5-1 part of nano-silicon dioxide.
2. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 1, characterized in that: The nano-silicon dioxide is hydrophobic nano-silicon dioxide pretreated with silane coupling agent KH-550, with a BET specific surface area of 150-200 m² / g and a purity of ≥99.8%, and the pretreatment process is as follows: the nano-silicon dioxide is added to a 6% silane coupling agent KH-550 ethanol solution, with a solid-liquid mass ratio of 1:8, stirred at 250 r / min for 30 min, and then dried in a 85°C vacuum drying oven for 3 h, and cooled for standby use.
3. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 1, characterized in that: The modified short fluorocarbon chain surfactant is prepared according to the following steps: A1, the perfluorohexyl ethyl acrylate copolymer is added to a three-necked flask containing ethanol, stirred at 200-250 r / min and heated to 60-70°C to completely dissolve it, hydroxyethyl methacrylate and ammonium persulfate are added, stirred uniformly, heated to 80-85°C and reacted for 4-5 h, cooled to room temperature, the product is precipitated with deionized water, the precipitate is filtered and dried in a 60-70°C vacuum drying oven for 8-10 h to obtain the first modified short fluorocarbon chain surfactant; A2, the first modified short fluorocarbon chain surfactant is added to a three-necked flask containing acetone, stirred at 200-250 r / min until completely dissolved and the temperature is controlled at 40-50°C, toluene diisocyanate is slowly added dropwise, the dropwise addition time is 1-1.5 h, stirring is performed at 150-200 r / min during the dropwise addition, after the dropwise addition is completed, stirring is continued to react for 2-3 h, then triethanolamine is added, heated to 60-65°C, and stirring is continued at 200-250 r / min for 3-4 h, after the reaction is completed, acetone is removed by distillation under reduced pressure to obtain the second modified short fluorocarbon chain surfactant; A3, the nano-titanium dioxide is added to a 1:1 volume ratio of ethanol-water mixed solvent, ultrasonic dispersion is performed for 30-40 min to form a uniform dispersion liquid, silane coupling agent KH-550 is added, stirred uniformly at 250-300 r / min, heated to 70-80°C and reacted for 2-3 h to obtain a nano-titanium dioxide dispersion liquid modified by the silane coupling agent, the second modified short fluorocarbon chain surfactant is added to the dispersion liquid, stirring is continued to react for 4-5 h, after the reaction is completed, the precipitate is collected by centrifugal separation, washed with ethanol for 3-4 times, and dried in a 80-90°C vacuum drying oven for 10-12 h to obtain the modified short fluorocarbon chain surfactant.
4. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 3, characterized in that: The amount ratio of the perfluorohexyl ethyl acrylate copolymer, ethanol, hydroxyethyl methacrylate and ammonium persulfate in A1 is 10-15 g:100-150 mL:30-40 g:2-3 g. The amount ratio of acetone, toluene diisocyanate, triethanolamine in A2 is 80-100 mL: 6-12 g: 5-8 g; The amount ratio of nano-titanium dioxide, ethanol-water mixed solvent, silane coupling agent KH-550 in A3 is 5-8 g: 100-120 mL: 3-5 g.
5. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 3, characterized in that: The toluene diisocyanate used in A2 is a mixture of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, the mass ratio of which is 3:1, and when toluene diisocyanate is added dropwise, the dropwise adding speed is controlled to be 0.5 mL / min through a constant pressure dropping funnel to ensure that the temperature fluctuation of the reaction system does not exceed ±2℃.
6. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 1, characterized in that: The modified guar gum is prepared according to the following steps: B1, the guar gum is added to a three-necked flask containing isopropyl alcohol and stirred uniformly at 200-250 r / min, sodium hydroxide is added, the temperature is raised to 50-60℃, and stirring is carried out at 150-200 r / min for 1-1.5 h, then propylene oxide is slowly added dropwise, the dropwise adding time is 1-2 h and the temperature is kept at 60-70℃, after the dropwise adding is completed, the reaction is continued at 70-75℃ for 3-4 h, after the reaction is completed, the pH is adjusted to neutral with hydrochloric acid, the filter cake is washed with isopropyl alcohol for 2-3 times, and drying is carried out in a vacuum drying box at 60-70℃ for 6-8 h to obtain the first modified guar gum; B2, the first modified guar gum is added to a three-necked flask containing deionized water, stirred at 250-300 r / min and heated to 70-80℃ to make it completely dissolved to form a uniform solution, acrylamide, potassium persulfate and N,N'-methylene bisacrylamide are added, after uniform stirring, nitrogen is introduced to remove air, and the reaction is carried out at 80-85℃ for 4-5 h under nitrogen protection, after the reaction is completed, the temperature is cooled to room temperature, the product is precipitated with ethanol, and after filtration, the precipitate is dried in a vacuum drying box at 70-80℃ for 8-10 h to obtain the second modified guar gum; B3, chitosan is added to a 1% acetic acid solution, stirred at 200-250 r / min until it is completely dissolved to form a chitosan acetic acid solution, the second modified guar gum is added to the solution and stirred uniformly, heated to 50-60℃, and glutaraldehyde is slowly added dropwise at a stirring speed of 150-200 r / min, after the dropwise adding is completed, the reaction is continued for 2-3 h, after the reaction is completed, the pH is adjusted to neutral with sodium hydroxide solution, the precipitate is collected by centrifugal separation, washed with deionized water for 3-4 times, and dried in a vacuum drying box at 60-70℃ for 8-10 h to obtain the modified guar gum.
7. An aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 6, characterized in that: The amount ratio of guar gum, isopropyl alcohol, sodium hydroxide and propylene oxide in B1 is 20-25 g: 90-110 mL: 2-3 g: 25-35 g; The amount ratio of deionized water, acrylamide, potassium persulfate and N,N'-methylene bisacrylamide in B2 is 80-100 mL: 15-25 g: 1-2 g: 0.5-1 g; The amount ratio of chitosan, acetic acid solution and glutaraldehyde in B3 is 5-8 g: 60-80 mL: 0.6-1 mL.
8. A process for the preparation of aqueous film forming foam extinguishing agent based on short fluorocarbon chains, characterized by: Specifically comprising the following steps: S1, the deionized water is purified by ion exchange resin for standby; nanometer silicon dioxide is dried in a vacuum drying oven at 100-110℃ for 2-3h for standby; S2, add purified deionized water in the reaction kettle, stirring at 200-300r / min, add dodecyl dimethyl betaine, ethylene glycol, benzotriazole, sodium bicarbonate, ethylenediaminetetraacetic acid disodium, isothiazolinone in turn, heat to 40-50℃ and stir for 30-40min to uniform; keep the speed, slowly add decabromodiphenyl ethane powder, stir to disperse uniformly; continue to keep the speed, slowly add sodium carboxymethyl cellulose, stir to form a uniform fluid and the viscosity at 40-50℃ reaches 100-300mPa•s, no visible particles or stratification; S3, add modified short fluorocarbon chain surfactant and modified guar gum to the above system, increase the stirring speed to 400-500r / min, heat to 60-70℃ and stir for 2-3h to uniform; add pretreated nanometer silicon dioxide, keep the speed and temperature and continue to stir for 1-1.5h to disperse uniformly; S4, add polydimethylsiloxane to the system and stir uniformly; then transfer the material to a high-pressure homogenizer, under the conditions of pressure 20-30MPa and temperature 50-60℃, each homogenization treatment time is 5-10min, homogenization treatment 2-3 times, to form a uniform and stable emulsion; S5, transfer the homogenized emulsion to a maturation tank, and stand at room temperature for maturation for 12-24h; after maturation, degas the emulsion at 40-50℃ under vacuum for 1-1.5h, the degassing vacuum degree is-0.08 to-0.09MPa, to remove the residual trace bubbles in the system; then filter with a 0.45μm filter membrane to remove impurities and particles not uniformly dispersed, and fill into a sealed container, to obtain a short fluorocarbon chain based water film forming foam extinguishing agent.
9. A process for the preparation of aqueous film forming foam extinguishing agent based on short fluorocarbon chains according to claim 8, characterized in that: The maturation process in S5 needs to be protected by nitrogen, the nitrogen flow is 0.5L / min, and the pressure in the maturation tank is maintained at 0.1MPa.
Citation Information
Cited By
Composite agent for inhibiting detonation of combustible gas and application
CN121846612A